Bivalirudin for Alternative Anticoagulation in Extracorporeal Membrane Oxygenation: A Systematic Review. (June 2017) - Sanfilippo, Filippo; Asmussen, Sven; Maybauer, Dirk M.; Santonocito, Cristina; Fraser, John F.; Erdoes, Gabor; Maybauer, Marc O.
Background: Extracorporeal membrane oxygenation (ECMO) offers therapeutic options in refractory respiratory and/or cardiac failure. Systemic anticoagulation with heparin is routinely administered. However, in patients with heparin-induced thrombocytopenia or heparin resistance, the direct thrombin inhibitor bivalirudin is a valid option and has been increasingly used for ECMO anticoagulation. We aimed at evaluating its safety and its optimal dosing for ECMO. Methods: Systematic web-based literature search of PubMed and EMBASE performed via National Health Service Library Evidence and manually, updated until January 30, 2016. Results: The search revealed 8 publications relevant to the topic (5 case reports). In total, 58 patients (24 pediatrics) were reported (18 received heparin as control groups). Bivalirudin was used with or without loading dose, followed by infusion at different ranges (lowest 0.1-0.2 mg/kg/h without loading dose; highest 0.5 mg/kg/h after loading dose). The strategies for monitoring anticoagulation and optimal targets were dissimilar (activated partial thromboplastin time 45-60 seconds to 42-88 seconds; activated clotting time 180-200 seconds to 200-220 seconds; thromboelastography in 1 study). Conclusion: Bivalirudin loading dose was not always used; infusion range and anticoagulation targets were different. In this systematic review, we discuss the reasons for this variability. Larger studies are needed to establish the optimal approach with the use of bivalirudin for ECMO.